Extracellular volume with bolus‐only technique in amyloidosis patients: Diagnostic accuracy, correlation with other clinical cardiac measures, and ability to track changes in amyloid load over time. Issue 6 (21st November 2017) - Zumbo, Giulia; Barton, Sharon V.; Thompson, Douglas; Sun, Min; Abdel‐Gadir, Amna; Treibel, Thomas A.; Knight, Daniel; Martinez‐Naharro, Ana; Thirusha, Lane; Gillmore, Julian D.; Moon, James C.; Hawkins, Philip N.; et al.
Abstract : Background: Extracellular volume (ECV) by T1 mapping requires the contrast agent distribution to be at equilibrium. This can be achieved either definitively with a primed contrast infusion (infusion ECV), or sufficiently with a delay postbolus (bolus‐only ECV). For large ECV, the bolus‐only approach measures higher than the infusion ECV, causing some uncertainty in diseases such as amyloidosis. Purpose: To characterize the relationship between the bolus‐only and current gold‐standard infusion ECV in patients with amyloidosis. Study Type: Bolus‐only and infusion ECV were prospectively measured. Population: In all, 186 subjects with systemic amyloidosis attending our clinic and 23 subjects with systemic amyloidosis who were participating in an open‐label, two‐part, dose‐escalation, phase 1 trial. Field Strength: Avanto 1.5T, Siemens Medical Solutions, Erlangen, Germany. Assessment: Bolus‐only and infusion ECV were measured in all subjects using shortened modified Look–Locker inversion recovery (ShMOLLI) T1 mapping sequence. Statistical Tests: Pearson correlation coefficient ( r ); Bland–Altman; receiver operating characteristic (ROC) curve analysis. Linear regression model with a fractional polynomial transformation. Results: The difference between the bolus‐only and infusion myocardial ECV increased as the average of the two measures increased, with the bolus‐ECV measuring higher. For an average ECV of 0.4, the difference was 0.013. The 95% limits of agreement for the two methods, after adjustment for the bias, were ±0.056. However, cardiac diagnostic accuracy was comparable (bolus‐only vs. infusion ECV area under the curve [AUC] = 0.839 vs. 0.836), as were correlations with other clinical cardiac measures, and, in the trial patients, the ability to track changes in the liver/spleen with therapy. Data Conclusion: In amyloidosis, with large ECVs, the bolus‐only technique reads higher than the infusion technique, but clinical performance by any measure is the same. Given the work‐flow advantages, these data suggest that the bolus‐only approach might be acceptable for amyloidosis, and might support its use as a surrogate endpoint in future clinical trials. Level of Evidence: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2018;47:1677–1684.